2010
DOI: 10.1111/j.1600-0625.2009.00990.x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of cathepsin S in psoriatic keratinocytes

Abstract: Cathepsin S (CATS) is a cysteine protease, well known for its role in MHC class II-mediated antigen presentation and extracellular matrix degradation. Disturbance of the expression or metabolism of this protease is a concomitant feature of several diseases. Given this importance we studied the localization and regulation of CATS expression in normal and pathological human ⁄ mouse skin. In normal human skin CATSimmunostaining is mainly present in the dermis and is localized in macrophages, Langerhans, T-and end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 77 publications
1
40
0
1
Order By: Relevance
“…Interestingly, a previous study using cathepsin S staining of biopsies has suggested that cathepsin S may be up-regulated in psoriatic lesions (30). To consolidate and quantify these findings, cathepsin S protein levels were analyzed in tape-strip samples acquired from the skin of psoriasis patients and healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a previous study using cathepsin S staining of biopsies has suggested that cathepsin S may be up-regulated in psoriatic lesions (30). To consolidate and quantify these findings, cathepsin S protein levels were analyzed in tape-strip samples acquired from the skin of psoriasis patients and healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…Cathepsin S is associated with inflammatory processes and chronic itch conditions. The expression of cathepsin S is upregulated in psoriatic keratinocytes [33]. Mice carrying a transgene expressing cathepsin S spontaneously develop atopic dermatitis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Increased cathepsin K expression in psoriatic lesion and the skin of K5.Stat3C mice Previous studies demonstrated increased levels of CTSs B, D, L, and S in psoriasis (19,20). We analyzed the expressions of Ctsk, Ctsb, Ctsl, and Ctss in human psoriasis (Fig.…”
Section: Resultsmentioning
confidence: 99%